An Informal Report to the Kansas Legislature, January 2009 - Cholick, Fred A. (My University, 2009)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2009, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN23_2009_01
Keywords: UNN23; Administrative and Research Reports; legislature